2016
DOI: 10.2134/agronj2016.02.0122
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia/Ammonium Toxicity Root Symptoms Induced by Inorganic and Organic Fertilizers and Placement

Abstract: Ammoniacal fertilizers can cause seedling damage. The present aims were to characterize spatial and temporal, root morphological NH3/NH4+ toxicity symptoms, assess the extent of the toxicity zone, and relate species‐specific responses to their root architecture. Wheat (Triticum aestivum L.) and canola (Brassica napus L.) were exposed to seed and deep placed urea. Faba (Vicia faba L) seedlings were grown above organic amendments. Time‐sequential images of canola root apex and root hair die‐back, discoloration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…The non‐proliferation zone as defined by the distance of root halt above the fertilizer band indicates the ability of the fertilizer to be transported up through the soil profile and be present in toxic concentrations at a given distance above the fertilizer band. Previous research demonstrates that the zone of non‐proliferation has been found to vary from 35 mm in maize with a below and to the side placed urea at 75 mg N cm –1 to 12 mm with urea banded directly below the seed at 19 mg N cm –1 (Pan et al, 2016; Creamer and Fox, 1980). The urea zone of non‐proliferation modeled in this study aligns well with previously reported results for canola (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The non‐proliferation zone as defined by the distance of root halt above the fertilizer band indicates the ability of the fertilizer to be transported up through the soil profile and be present in toxic concentrations at a given distance above the fertilizer band. Previous research demonstrates that the zone of non‐proliferation has been found to vary from 35 mm in maize with a below and to the side placed urea at 75 mg N cm –1 to 12 mm with urea banded directly below the seed at 19 mg N cm –1 (Pan et al, 2016; Creamer and Fox, 1980). The urea zone of non‐proliferation modeled in this study aligns well with previously reported results for canola (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity symptoms have been detected both on the roots and shoots of many crop species (Dowling, 1998). The root apex and its axis has been shown to dieback on direct encounter with the fertilizer reaction zone (FRZ) (Pan et al, 2016). As a result, placement of ammoniacal N fertilizer below the seed increases the likelihood for root dieback to occur.…”
mentioning
confidence: 99%
See 3 more Smart Citations